Arqueologia de la Cuenca del Qaracha, Ayacucho, Peru - Valdez, Lidio M.; Vivanco, Cirilo (My University, 1994)
In order to evaluate the Precolumbian occupation of the Qaracha Basin (Ayacucho, Peru), we carried out an archaeological survey in 1988, which yielded evidence of three main occupations, the first under Wari domination ca. A.D. 600, with settlements located 2,800-3,650 m asl, in control of farmland linked to corn cultivation. Around A.D. 900 the Wari sites were abandoned, and new fortified sites were built in strategic positions in the upper elevations. Inka control of the central Andes brought about abandonment of the fortified sites and the founding of new Inka sites (mitimaes) near the ancient Wari sites. We believe that the first change was tied to collapse of the Wari state, which was followed by an unsettled situation in which former elements of the Wari state were at war. The final change ended the chaotic period with the birth of the Inka state in the Andes.
Archeology of the Qaracha Basin, Ayacucho, Peru
Keywords: Inka; Andes; Peru; archaeological sites